Preventive conservation of documents - Calderón Delgado, Marco A (2008)
Paper documents undergo constant changes in their physical and functional composition, which endangers the information contained in them. This document defines some basic notions regarding the subject, addresses the composition and structure of paper, as well as the intrinsic and extrinsic causes of its degradation. Finally, preventive methods are proposed for the conservation of documents in the different information units.